Descripción e identificación de occisos registrados por medicina legal del Valle del Cauca por medio de carta dental en la base de datos en medicina legal (2022)
To describe, through the dental chart, the unidentified deceased, registered by legal medicine in Valle del Cauca for comparison and possible identification.